2020
DOI: 10.1038/s41419-020-03115-3
|View full text |Cite
|
Sign up to set email alerts
|

BCL11B suppresses tumor progression and stem cell traits in hepatocellular carcinoma by restoring p53 signaling activity

Abstract: Accumulating evidence indicates that hepatocellular carcinoma (HCC) tumorigenesis, recurrence, metastasis, and therapeutic resistance are strongly associated with liver cancer stem cells (CSCs), a rare subpopulation of highly tumorigenic cells with self-renewal capacity and differentiation potential. Previous studies identified B cell leukemia/lymphoma-11b (BCL11B) as a novel tumor suppressor with impressive capacity to restrain CSC traits. However, the implications of BCL11B in HCC remain unclear. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…It highlighted the crucial function of BCL11B, which is increased after ACSL4 overexpression, in lipid metabolism. Yang et al reported that BCL11B expression greatly sensitizes HepG2 and Huh7 hepatocarcinoma cell lines towards doxorubicin [50] . Besides, the signaling transduction factor GDF15, which is a secreted cytokine of TGF-β superfamily, is decreased after ACSL4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…It highlighted the crucial function of BCL11B, which is increased after ACSL4 overexpression, in lipid metabolism. Yang et al reported that BCL11B expression greatly sensitizes HepG2 and Huh7 hepatocarcinoma cell lines towards doxorubicin [50] . Besides, the signaling transduction factor GDF15, which is a secreted cytokine of TGF-β superfamily, is decreased after ACSL4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic liver transplantation (OLT) and surgical resection are known as the most effective approaches for HCC treatment. However, a high rate of metastasis/recurrence (~50%–70%) has been observed within five years post‐operation 7 . Although sorafenib and regorafenib are used as the first‐ and second‐line systemic chemotherapy for HCC, concerns about drug resistance, which leads to a high mortality rate, are rising.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high rate of metastasis/recurrence (~50%–70%) has been observed within five years post‐operation. 7 Although sorafenib and regorafenib are used as the first‐ and second‐line systemic chemotherapy for HCC, concerns about drug resistance, which leads to a high mortality rate, are rising. Over the recent decades, a large body of evidence has been obtained about the role played by genes crucial for cellular processes, such as cell cycle control, cell growth, apoptosis and migration in HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting was performed following previous studies [14]. The utilized antibodies included anti-THRSP (1:500, sc-516102; Santa Cruz), anti-phospho-ERK (Tyr202/Tyr204) (1:1000, 4377S; CST), anti-ERK (1:1000, 4695S; CST), anti-Slug (1:1000, 9585S; CST), anti-Snail (1:1000, 3879S; CST), anti-Twist (1:1000, 46702S; CST), anti-ZEB1 (1:1000, 70512S; CST), anti-ZEB2 (1:1000, 3396S; CST).…”
Section: Western Blotmentioning
confidence: 99%